1998
DOI: 10.1029/98jd02459
|View full text |Cite
|
Sign up to set email alerts
|

Estimating vegetation structural effects on carbon uptake using satellite data fusion and inverse modeling

Abstract: Abstract. Regional analyses of biogeochemical processes can benefit significantly from observational information on land cover, vegetation structure (e.g., leaf area index), and biophysical properties such as fractional PAR absorption. Few remote sensing efforts have provided a suite of plant attributes needed to link vegetation structure to ecosystem function at high spatial resolution. In arid and semiarid ecosystems (e.g., savannas), high spatial heterogeneity of land cover results in significant functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Collectively, these studies indicate a positive relationship at regional scales between woody plant-induced increases in ecosystem C-sequestration potential and mean annual rainfall. Approaches such as the one used here, which link remote sensing, field sampling, and ecosystem modeling, are emerging as plausible means for addressing this complexity (Wessman 1992, Asner et al 1998, Akiyama and Koizumi 2002 These contrasting perspectives point to the need for a better understanding of how ecosystem primary production and SOC pools change with replacement of grasses by woody plants (e.g., House et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies indicate a positive relationship at regional scales between woody plant-induced increases in ecosystem C-sequestration potential and mean annual rainfall. Approaches such as the one used here, which link remote sensing, field sampling, and ecosystem modeling, are emerging as plausible means for addressing this complexity (Wessman 1992, Asner et al 1998, Akiyama and Koizumi 2002 These contrasting perspectives point to the need for a better understanding of how ecosystem primary production and SOC pools change with replacement of grasses by woody plants (e.g., House et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the community of vegetation mapping, most studies focus on the sunlit portions of the upper canopy and discard the shaded portions in subsequent spectral analysis [5,6,7,8,9,10,11]. Others assume that the reflectance values of shadows equal zero or are constant for the purposes of spectral mixture analysis [2,12] and estimation of canopy parameters with radiative transfer [13,14] or geometrical optical models [15,16,17]. These studies suggest that the potential spectral information in shaded portions of the canopy have not been fully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the physically based domains of EMs provide a more intuitive link between image measurements and observations in the field (Adams et al 1995), and fractions modelled by LSMA of TM images have been linked to biophysical parameters of vegetation in boreal forest and savannah ecosystems (e.g. Hall, Shimabukuro, and Huemmerich 1995;Asner et al 1998;Peddle, Brunke, and Hall 2001). Hall, Shimabukuro, and Huemmerich (1995) and Sonnentag et al (2007) found the excellent shade fraction models for mapping tree and shrub leaf area indices (LAIs).…”
Section: Introductionmentioning
confidence: 99%